Shaping memory consolidation via targeted memory reactivation during sleep. Issue 1 (15th May 2018) - Cellini, Nicola; Capuozzo, Alessandra
Abstract: Recent studies have shown that the reactivation of specific memories during sleep can be modulated using external stimulation. Specifically, it has been reported that matching a sensory stimulus (e.g., odor or sound cue) with target information (e.g., pairs of words, pictures, and motor sequences) during wakefulness, and then presenting the cue alone during sleep, facilitates memory of the target information. Thus, presenting learned cues while asleep may reactivate related declarative, procedural, and emotional material, and facilitate the neurophysiological processes underpinning memory consolidation in humans. This paradigm, which has been named targeted memory reactivation, has been successfully used to improve visuospatial and verbal memories, strengthen motor skills, modify implicit social biases, and enhance fear extinction. However, these studies also show that results depend on the type of memory investigated, the task employed, the sensory cue used, and the specific sleep stage of stimulation. Here, we present a review of how memory consolidation may be shaped using noninvasive sensory stimulation during sleep. Abstract : The reactivation of specific memories during sleep can be modulated using external stimulation, e.g. by matching a sensory stimulus with target information during wakefulness, and then presenting the cue alone during sleep. Presenting learned cues while asleep may facilitate the neurophysiological processes underpinning memory consolidation in humans. Here we present a review of how memory consolidation may be shaped using non‐invasive sensory stimulation during sleep.